AGRARIAN REFORMS UNDERTAKEN BY THE SOVIET GOVERNMENT IN UZBEKISTAN AND THEIR SOCIETAL CONSEQUENCES (1950s – 1960s) - Mamajanov Azizbek Alisher ugli (Sciental Journals Publishing, 2025)
The article reflects the agrarian policy of the Soviet government towards Uzbekistan in the late 50s and early 60s of the twentieth century. The inconsistency of the reforms carried out under the leadership of N. S. Khrushchev is shown. The inefficiency of the development of virgin lands, which, as all historians admit, was carried out by extraordinary state measures, forcibly, is shown. It also led to a sharp depletion of the fertile layer. The low standard of living of the peoples of Central Asia. The article describes the activities carried out in Uzbekistan, the result of which led to further monopolization of cotton culture and exacerbation of the environmental problem.
Keywords: Agrarian reform, cotton monoculture, party, cellinik, agrogrod